Cavity Disinfection With a 445 nm Diode Laser Within the Scope of Restorative Therapy – A Pilot Study - Lusche, Inés; Dirk, Cornelius; Frentzen, Matthias; Meister, Joerg (Journal of Lasers in Medical Sciences, 2020)
Introduction: Cavity disinfection is necessary to prevent a progressive infection of the crown dentin and pulp. Increasing intolerance and resistance to antiseptics and antibiotics as well as the controversy over the effects of those on the dental hard tissue and composite have prompted the investigation of alternative treatment options. The objective of this pilot study is to evaluate the antibacterial potential of a diode laser with a wavelength of 445 nm in the cavity preparation using the bacterium Streptococcus salivarius associated with caries in conjunction with the characteristics and influences of dentin on light transmission. Methods: The bactericidal effect of the laser irradiation was determined in culture experiments by using caries-free human dentin samples on bacteria-inoculated agar. For this, dentin discs (horizontally cut coronal dentin) of 500 μm and 1000 μm thicknesses were produced and irradiated with the laser with irradiation parameters of 0.7-1 W in a cw-mode and exposure times of between 5-30 s. Based on the different sample thicknesses, the penetration depth effect of the irradiation was ascertained after the subsequent incubation of the bacteria-inoculated agar. Additional influential parameters on the irradiation transmission were investigated, including surface moisture, tooth color as well as the presence of a smear layer on the dentin surface. Results: The optical transmission values of the laser radiation for dentin were significantly dependent on the sample thickness (P = 0.006) as well as its moisture content (P = 0.013) and were independent of the presence of a smear layer. There was a 40% reduction in bacteria after the radiography of the 500-μm-thick dentin samples, which was shown as the lowest laser dose (443 J/cm2). Conclusion: These findings indicate that the diode laser with light emission at a wavelength of 445 nm is interesting for the supportive cavity disinfection within the scope of caries therapy and show potential for clinical applications.